How can pure social discounting be ethically justified? - Buchholz, Wolfgang; Schymura, Michael (Mannheim, 2013)
"The evaluation of long-term eects of climate change in cost-benet analysis has a long tradition in environmental economics. Since the publication of the Stern Review in 2006 the debate about the "appropriate" discounting of future welfare and utility levels was revived and the most renowned scholars of the profession participated in this debate. In two recent contributions in Environmental and Resource Economics, there was dispute about intertemporal welfare economics between Partha Dasgupta and John Roemer about the correct interpretation of the topic. The aim of this work is to bring together economic and philosophical reasoning about justice and intergenerational equity in the context of climate change. So we adopt the normative view in order to present the most important ethical issues that, particularly in the context of climate policy, are most relevant for the choice of intertemporal discounting. Subsequently we explore whether ethical considerations may also be helpful to justify pure social discounting per se."